Mechanisms of Glaucoma in Exfoliation Syndrome. Issue 7 (July 2018) - Ozaki, Mineo
Abstract : The most important characteristic of exfoliation syndrome (XFS) is that it involves a greater risk of developing glaucoma. In comparison with other forms of open-angle glaucoma, exfoliation glaucoma is more resistant to medical therapy and progresses faster. Possible pathologic mechanisms of glaucoma development in XFS comprise: (1) elevated intraocular pressure (IOP) caused by functional impairment of aqueous humor outflow due to deposition of exfoliation material in the trabecular meshwork and trabecular cell dysfunction, (2) XFS-associated connective tissue elastosis leading to structural and functional alterations of the lamina cribrosa which increases the vulnerability toward elevated IOP and development of glaucomatous optic neuropathy, (3) elevated IOP due to closure of the anterior chamber angle accompanied by forward displacement of the crystalline lens due to zonular weakness, (4) presumable primary functional impairment of retinal ganglion cells. In addition to the discovery of lysyl oxidase-like 1, further genetic associations have been identified and knowledge related to XFS etiology and pathophysiology has markedly increased over the past 10 years. Further cell biological investigations navigated by the molecular genetics underlying XFS will eventually lead to a better understanding of the complex mechanisms of exfoliation glaucoma.